2015
DOI: 10.1080/14786419.2014.1000321
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, structure elucidation and enzyme inhibition studies of a new hydroxy ester and other compounds fromBerberis jaeschkeanaSchneid stem

Abstract: Bioassay-guided isolation and fractionation of Berberis jaeschkeana Schneid var. jaeschkeana stem resulted in the isolation and characterisation of a new long chain hydroxy ester named as berberinol (1) along with six known compounds (2-7). All the structures were established from 1D and 2D spectroscopic data. Crude extract, sub-fractions and all the isolated compounds were evaluated for their anti-fungal and urease enzyme inhibition properties. All of the sub-fractions and compounds showed good anti-fungal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Using maceration and methanol techniques for Berberis aetnensis and Berberis libanotica extraction yields were 8.9 and 7.6%, respectively, as specified by Bonesi [83]. Likewise, for Berberis jaeschkeana a 4.5% extraction yield was described when using maceration with methanol [84]. For Berberis darwinii yields were 9.5 and 1.5% by maceration and infusion using methanol and water respectively [85].…”
Section: Extraction and Fractionationmentioning
confidence: 99%
“…Using maceration and methanol techniques for Berberis aetnensis and Berberis libanotica extraction yields were 8.9 and 7.6%, respectively, as specified by Bonesi [83]. Likewise, for Berberis jaeschkeana a 4.5% extraction yield was described when using maceration with methanol [84]. For Berberis darwinii yields were 9.5 and 1.5% by maceration and infusion using methanol and water respectively [85].…”
Section: Extraction and Fractionationmentioning
confidence: 99%
“…brucei effectively. 32 Molecular docking analyses showed that bisbenzylisoquinoline alkaloids (BBIQ) possessed certain structural motifs (extensive van der Waals interactions and hydrogen bonding) that could exhibit the best binding properties with multiple T. brucei drug targets (trypanothione reductase, rhodesain, farnesyl diphosphate synthase, and triosephosphate isomerase). 33 Thus, we have evaluated curine derivatives 1−4 against the druggable protein targets of T. brucei from the Protein Data Bank (PDB).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Berberine (WA1), palmatine (WA2), and 8-trichloromethyl dihydroberberine (WA3) used in this investigation were extracted from B. glaucocarpa Stapf, and the spectroscopic results agree with previously published literature. 32 Streptozotocin, Tween-80, α-glucosidase, and substrate (p-nitrophenylα-D-glucopyranoside) were bought from Sigma-Aldrich in Germany. The local pharmaceutical company provided the glibenclamide.…”
Section: Methodsmentioning
confidence: 99%